In the pursuit of social justice during political transitions: the practices of CSOs in post-Arab Spring Tunisia - Fethi Mansouri; Rebecca Buys; Amanuel Elias (Cogent Social Sciences, 2024)
While social inequalities and regional disparities incited Tunisia’s 2011 so-called ‘Jasmine Revolution’, successive government promises to improve the lives of the country’s most marginalized people remain unfulfilled. This article explores the role of local Tunisian civil society organizations (CSOs) in compensating for the state’s lack of social justice reform and equitable regional development during the COVID-19 pandemic and growing political unrest. Our findings show that during periods of significant upheaval, civil society rapidly changes to assume increasingly diverse and essential roles in providing care and safety for vulnerable people and their communities, but this responsiveness is not without difficulty. Attempts at understanding civil societies’ emergent and dynamic functions needs to be deeply contextualized to incorporate the dynamic politics of democratic transitions and entanglements vis-à-vis the state in processes of change. By bringing attention to these relational entanglements, complexities and dynamic state-civil society-citizen struggles participants emphasized, our findings challenge homogenizing and normative theoretical approaches to civil society.